Pelatihan Perencanaan Usaha dan Komunikasi Publik Koperasi Desa Merah Putih Huta Baringin - Fitri, Sari; Ardiansyah, Muhammad; Farid, Ahmad Salman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This community service activity was implemented using a service learning approach through a business planning and public communication training program for the Merah Putih Village Cooperative in Huta Baringin. The background to this activity stems from the need for cooperative members to increase their capacity in designing sustainable business plans and effective public communication skills in conveying the cooperative's vision, mission, and programs to the community. The implementation method was carried out through the stages of needs identification, formulation of training materials, simulation practices, and intensive mentoring. The results of the activity showed an increase in cooperative members' understanding in developing business plans based on local potential and improved public communication skills, both within the organizational context and externally to strategic partners. This program not only strengthens the cooperative's independence but also demonstrates the relevance of the service learning model in connecting the roles of academics, students, and the community collaboratively. Thus, this training contributes to local economic empowerment and strengthening institutional communication capacity at the village level.